Pengaruh Leverage, Struktur Modal, dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Sektor Pertambangan - Wiwi Widyas Hasti; Maryani Maryani; Arif Makshun (Reviu Akuntansi, Manajemen, dan Bisnis, 2022)
Purpose: This study aims to determine the effect of leverage, capital structure and company size on the financial performance of mining sector companies listed on the Indonesian stock exchange during the Covid-19 pandemic. Methodology: The sampling method used was a purposive sampling technique with a sample of mining sector companies listed on the Indonesia Stock Exchange (IDX) during the co-19 pandemic. The analytical tool used in this study is multiple linear regression analysis. Data were analyzed using SPSS version 22. Results: The results of this study indicate that leverage has a negative effect on financial rformance, capital structure has no effect on financial performance, and firm size has no effect on financial performance. Limitations: This study only uses three independent variables while there are many other an be used to influence financial performance. Contribution: This research is expected to be able to contribute to the development of accounting theory and become a reference source for further research related to accounting.